IDENTIFICATION OF DETERMINANT FACTORS IN ELDERLY WITH HYPERTENSION - Restawan, I Gede; Sjattar, Elly Lilianty; Irwan, Andi Masyitha (Jurnal Kesehatan, 2023)
The number of elderly people is increasing. Healthy elderly will have an impact on the success of health development. On the other hand, many elderly people suffer from hypertension and cause problems both in their health and there is an increase in dependence on productive age. This study aims to identify the determinant factors in the elderly with hypertension so that they can be indicators of hypertension prevention. This study used a quantitative descriptive research design with a cross sectional approach. The number of samples is the total elderly population in STIKes BK Palu who suffer from hypertension as many as 50 respondents. The results of this study were tested using Kendall's tau-b test. The results showed that the determinant factors that correlated with the degree of hypertension were age, occupation, marital status and level of depression. Of the four, the level of depression is the strongest correlation factor. This is closely related to adherence in taking antihypertensive drugs. Thus, there needs to be a role and contribution from both health workers and the community to improve health education and health literacy about hypertension in order to prevent an increase in blood pressure in people with hypertension.